Further spectral and chromatographic studies of ambergris - Rowland, S.; Sutton, P.; Belt, S.; Fitzsimmons-Thoss, V.; Scarlett, Alan (Taylor & Francis, 2018)
Jetsam ambergris, found washed ashore on beaches, is an environmentally modified form of a natural product of Sperm whales which sometimes develops a pleasant odour. Odorous samples have proved valuable in perfumery. Identification of jetsam ambergris by analysis of organic-soluble extracts by Fourier transform infra-red spectroscopy (FTIR) and of derivatised samples by gas chromatography-mass spectrometry (GC-MS) has already been shown. Here, we describe a different method, in which characteristic alkenic protons and carbon atoms of the major constituent ambrein, were identified in whole extracts using nuclear magnetic resonance spectroscopy (NMR). The advantages of employing NMR spectroscopy included rapidity, reduced losses of volatiles compared to GC-MS and detection of non-GC amenable constituents. However, the identities and quantities of co-occurring individual components (e.g. steroids) could not easily be assigned in the unfractionated extracts by NMR spectroscopy, whereas they were by GC-MS, so an approach combining FTIR, GC-MS and NMR spectroscopic methods is advocated.